2011
DOI: 10.1080/09593330.2011.560615
|View full text |Cite
|
Sign up to set email alerts
|

A review of the use of red mud as adsorbent for the removal of toxic pollutants from water and wastewater

Abstract: Red mud (an aluminium industry waste) has received wide attention as an effective adsorbent for water pollution control, showing significant adsorption potential for the removal of various aquatic pollutants. In this review, an extensive list of red-mud-based adsorbents has been compiled and their adsorption capacities (maximum uptake value of the adsorbent for the pollutant or adsorbate being removed) for various aquatic pollutants (metal ions, dyes, phenolic compounds, inorganic anions) are presented. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(102 citation statements)
references
References 93 publications
(94 reference statements)
2
86
0
5
Order By: Relevance
“…It is evident from the studied literature (Kurdowski & Sorrentino, 1997;Andrejcak & Soucy, 2004;Liu, Y. et al, 2011;Paramguru et al, 2005;Bhatnagar et al, 2011;Klauber et al, 2009) Table 3. Overview of BR application areas from the alumina production.…”
Section: Exploitation Possibilitiesmentioning
confidence: 83%
“…It is evident from the studied literature (Kurdowski & Sorrentino, 1997;Andrejcak & Soucy, 2004;Liu, Y. et al, 2011;Paramguru et al, 2005;Bhatnagar et al, 2011;Klauber et al, 2009) Table 3. Overview of BR application areas from the alumina production.…”
Section: Exploitation Possibilitiesmentioning
confidence: 83%
“…Both metallurgical slag and red mud are common metallurgical wastes. Some researchers have proposed a number of applications in order to recycle them, such as environmental remediation, metal recovery, and production of various materials including building materials, polymers and ceramics (Amorim et al, 2012;Bhatnagara et al, 2011;Costa et al, 2010;Liu et al, 2009;Liu and Zhang, 2011;Paramguru et al, 2005;Pontikes and Angelopoulos, 2013). The advantage of the procedure proposed in this study is quite obvious since it combines recycling with the synthesis of a high added value material, efficient for environmental remediation, contributing in that way to sustainable development.…”
Section: Introductionmentioning
confidence: 89%
“…RM is a high-pH alkaline substance (Bhatnagar et al 2011). From this study, the changes in pH with the concentration of RM were observed for 12 hours.…”
Section: Effect On Phmentioning
confidence: 95%
“…However, due to its high alkalinity, RM has high pH levels ranging between 10 and 13. Moreover, RM contains high proportions of aluminum, iron, silicon, titanium oxides, and hydroxides, thus RM could be toxic to the environment (Bhatnagar et al 2011). Bioassay tests have been widely used for evaluating toxicity in a variety of aquatic organisms.…”
Section: +mentioning
confidence: 99%